Coexistence and habitat partitioning at micro- and macro-scales of rodent species in a North African desert (Bou-Hedma National Park, Tunisia). (August 2016) - Traba, Juan; Casals, Pere; Broto, Ferran; Camprodon, Jordi; Giralt, David; Guixé, David; Mechergui, Rania; Rios, Ana; Sales, Sergi; Taull, Marc; Ammari, Youssef; Solano, David; et al.
Abstract: Deserts rodents coexistence has been mainly attributed to resource partitioning at different scales, from macro to microhabitat. We explore the structure of a rodent community in a North African desert under the hypothesis of resource partition. We present the first data of habitat selection by several Gerbilline rodent species in North Africa (Tunisia). Animals were trapped during one season in four locations of the Tunisian desert (Bou-Hedma National Park). Macrohabitat selection was assessed by RDA and variance partitioning. The effect of macrohabitat variables on species richness was assessed by Poisson GLZ and multimodel averaging. Microhabitat selection was evaluated by GLMM and multimodel averaging. Our results support the configuration of two desert rodents assemblages in this region: one characterized by species requiring disaggregated soil, probably for burrowing necessities ( Gerbillus tarabuli, Meriones crassus, Gerbillus campestris ); and the other one characterized by species maximizing shrub cover, presumably related to food availability and predation risk ( Meriones shawii and Gerbillus amoenus ). Gerbillus gerbillus seems to have a specially distinctive microhabitat selection pattern. Our results at the microhabitat scale highlight the role that floristic composition can play to segregate between rodent species. Highlights: Exploring the habitat selection of desert North African rodents is proposed. Both macro and microhabitat scales were analysed. Low resource availability probably causes low capture rates. Two assemblages were found, a soil-dependant and a food availability-dependant. North African desert rodent species can also segregate by floristic preferences.